A study of hysteresis in perovskite solar cell. (2016) - Yan, Qiaojing; Rui, Xianfeng; Li, Heng; Yu, Dapeng; Zhao, Qing
Hybrid lead-halide perovskite solar cells (PSCs) have become the hot spot in photovoltaic domain since 2012. Although perovskite solar cells exhibit high power conversion efficiencies (PCE), some unsolved issues remain in the measurement of device performance, especially the abnormal hysteresis in current-voltage scan. The hysteresis phenomena result in the overstatement of the performance of PSCs during backward scan, which starts from the bias higher than open voltage and sweep to voltage below zero. In steady output, the stabilised PCE is lower than the dynamic outcome, such as the maximum power point in the I-V curve. The origin of this abnormal hysteresis is under debate. Here, we introduced a model to explain the dependence of I-V measurements on scan history. According to computational simulations using semiconductor transport theories, we found that the experimental results were consistent with the model based on the polarisation of perovskite materials. The bias-induced polarisation affects both the heterojunction resistance and the magnitude of light-generated current. By analysing current results, we supports the view that polarisation is caused by internal ion migration rather than ferroelectricity.